Giant follicular cyst of ovary in an adolescent girl - Jayakumar; Ravichandran, Vidhya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ovarian cystadenomas are rare neoplastic tumors arising from the ovarian surface epithelium. While commonly observed in adult women, their occurrence in adolescents is extremely uncommon. Now, those lesions diagnosed more frequently due to availability of better imaging modalities. Presentations as huge cysts have become rare as most of them are diagnosed and treated early. Adolescent girls presenting with huge benign abdominal cysts are uncommon, most of them due to serous cystadenomas of the ovary, but large follicular cysts are rare. We present a 13year old girl who presented with a large abdominal mass which was subsequently diagnosed as juvenile follicular cyst of the ovary. Urgent surgical intervention led to left salpingo-oophorectomy, confirming the benign nature of the tumor. This report highlights the importance of comprehensive approach to diagnosing and managing rare ovarian neoplasms in adolescents.